Body temperature, heart rate, and activity patterns of two boreal homeotherms in winter: Homeostasis, allostasis, and ecological coexistence. (26th August 2020) - Menzies, Allyson K.; Studd, Emily K.; Majchrzak, Yasmine N.; Peers, Michael J. L.; Boutin, Stan; Dantzer, Ben; Lane, Jeffrey E.; McAdam, Andrew G.; Humphries, Murray M.
Abstract: Organisms survive environmental variation by combining homeostatic regulation of critical states with allostatic variation of other traits, and species differences in these responses can contribute to coexistence in temporally variable environments. In this paper, we simultaneously record variation in three functional traits—body temperature ( T b ), heart rate and activity—in relation to three forms of environmental variation—air temperature ( T a ), photoperiod and experimentally manipulated resource levels—in free‐ranging snowshoe hares and North American red squirrels to characterize distinctions in homeotherm responses to the extreme conditions of northern boreal winters. Hares and squirrels differed in the level and precision of T b regulation, but also in the allostatic pathways necessary to maintain thermal homeostasis. Hares demonstrated a stronger metabolic pathway (through heart rate variation reflective of the thermogenesis), while squirrels demonstrated a stronger behavioural pathway (through activity variation that minimizes cold exposure). As intermediate‐sized, winter‐active homeotherms, hares and squirrels share many functional attributes, yet, through the integrated monitoring of multiple functional traits in response to shared environmental variation, our study reveals many pairwise species differences in homeostatic and allostatic traits, that both define and are defined by the natural history, functional niches and coexistence of sympatric species. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.